FASIITIS NEKROTIKAN TIPE II - Sondakh, Oktavia R. L.; Tangkidi, Damayanti; Pandaleke, Herry E. J. (Jurnal Biomedik : JBM, 2015)
Abstract: Necrotizing fasciitis, often called flesh eating bacteria, is a progressive necrosis in subcutaneous fat and fascia. Type II necrotizing fasciitis caused by Acinetobacter baumannii is rarely found. Predisposing factors of necrotizing fasciitis include elderly, immunocompromised condition, chronic diseases, alcoholism, and trauma. We reported a case of a 68-year-old male complained of dark red swelling accompanied by pain in the left thigh. On examination of the left femoral region, there was a diffuse macula, plaque sized, erythematous to black colored, with erosion, excoriation, and necrotic tissue. Hematological examination showed the LRINEC score of 6. The pus culture result was Acinetobacter baumannii. The patient was given systemic antibiotics and debriedement was performed. The lesion did not extend anymore and the patient's general condition became better. Post debridement, the ulcer was treated with hydrogel wound dressings containing honey. After 60 days, the ulcer healed with a hypertrophic scar. Conclusion: This case was diagnosed as type II necrotizing fasciitis caused by Acinetobacter baumannii based on anamnesis, physical examination, hematological examination, and pus culture which were typical for this diagnosis.Keywords: type II necrotizing fasciitis, LRINEC scoreAbstrak: Fasiitis nekrotikan (FN) atau sering disebut â€œflesh eating bacteriaâ€ adalah nekrosis progresif di lemak sub kutan dan fasia. Fasiitis nekrotikan tipe II yang disebabkan oleh Acinetobacter baumanii jarang ditemukan. Faktor predisposisi FN antara lain usia lanjut, imunokompromais, penyakit kronik, alkoholisme, dan trauma. Kami melaporkan seorang laki-laki berusia 68 tahun dengan bengkak merah kehitaman yang disertai nyeri di paha kiri. Pada pemeriksaan regio femoralis sinistra terdapat makula difus, ukuran plakat, eritem sampai kehitaman, disertai erosi, eskoriasi, dan jaringan nekrotik. Pemeriksaan hematologik menunjukkan skor LRINEC 6. Hasil kultur pus ialah Acinetobacter baumanii. Pasien mendapatkan antibiotik sistemik dan dilakukan debrideman. Lesi tidak meluas dan keadaan umum pasien baik setelah penanganan dengan antibiotik dan debrideman. Ulkus paska debrideman dirawat dengan balutan luka hidrogel mengandung madu. Ulkus sembuh dengan meninggalkan skar hipertrofik setelah 60 hari. Simpulan: Pada kasus ini, diagnosis fasiitis nekrotikan tipe II yang disebabkan oleh Acinetobacter baumanii ditegakkan berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan hematologik, dan kultur pus yang khas.Kata kunci: fasiitis nekrotikan tipe II, skor LRINEC